Implementing Adaptive Data Governance: A Technical Perspective - Prem Kumar Tamanam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and implementation of adaptive data governance frameworks in modern enterprises. The article examines critical components, including metadata management, policy enforcement, and monitoring systems across multiple organizational contexts. Through a detailed examination of implementation patterns, security controls, and performance optimization strategies, the article demonstrates the significant impact of adaptive governance on operational efficiency, compliance management, and risk mitigation. The article encompasses technical architecture considerations, implementation frameworks, best practices, and future-proofing strategies, providing insights into successful governance transformations across diverse industry sectors.
Keywords: Adaptive Data Governance; Enterprise Architecture; Policy Enforcement; Risk Mitigation; Performance Optimization